SISTEM INFORMASI PEMINJAMAN ASET PEGAWAI BERBASIS WEBSITE STUDI KASUS PT XYZ - Kamila, Alya Hasna; Kusumawardhani, Damar; Siahaan, Sekar Griselda Nadine; Uli, Tresia Shinta; Maulita, Wike Mawar; Krisnanik, Erly; Mardiah (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2025)
Managing asset lending is a crucial aspect of employee productivity. However, many organizations, including PT XYZ, still rely on semi-manual methods like Google Forms. This approach is prone to errors, data loss, and tracking difficulties, leading to operational inefficiencies and hampered decision-making. Specific issues at PT XYZ include poor documentation, difficulty tracking assets, and a lack of real-time access to asset availability information. This research aims to thoroughly analyze the existing problems in PT XYZ's asset lending and return process, formulate effective solutions, and design a web-based asset lending information system that aligns with the company's operational needs. The research stages include observation, interviews, system requirements analysis, and the design of the proposed system. This information system is expected to overcome the limitations of manual methods by supporting systematic record-keeping, facilitating tracking, and providing real-time access to asset information.